Disagio moderno e etica dell’autenticità. Tra Taylor e Montale - Neri, Veronica (Bollettino Filosofico, 2017)
Individualism, authenticity and modern-day social imaginary represent some of the dimensions of our Western modernity. These are dimensions that philosophy and poetry have been reflecting on since the second half of the 20th century in order to better understand the identity of the self. Montale and Taylor, two authors who are oceans apart, both in terms of geography and of spiritual vision, have both tackled the problems associated with the loss of the “horizons of sense” on the part of the individual within this context. Both believe that language is the tool for redefining the ethics of modern authenticity, without falling into dangerous radicalization, and leading to perspectives which are, in part, different: the Italian poet sees only a nonsense in life, whereas the Canadian philosopher opts for a return to the transcendental experience, in the religious sense, one that our “secular age” does not always make self-evident.